2008
DOI: 10.4314/bcse.v22i1.61351
|View full text |Cite
|
Sign up to set email alerts
|

<b>Investigation of chemical and biochemical properties of <i>Maerua subcordata</i>

Abstract: This paper reports some findings of chemical as well as biochemical studies of Maerua subcordata plant juice extract. The studies include: chemical composition of the juice such as mineral contents, protein and polysaccharide contents. These tests were carried out both in the juice extracts and in the "flocs". The latter samples were analyzed to establish whether the material that settled as a result of clarification had minerals, protein and/or polysaccharides. While there were no significant amounts of miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
8
0
2
Order By: Relevance
“…Gomas (galactomananos) de semilla de Cassia obtusifolia también se han utilizado para la remediación de aguas residuales de aceite de palma (Shak & Wu, 2014), así como las gomas de semillas de Cassia angustifolia para la remoción de colorantes (Sanghi, Bhatttacharya, & Singh, 2002). Además, a polisacáridos como la amilopectina extraída del jugo de tubérculos de Maerua subcordata se atribuye el efecto coagulante para la clarificación de agua superficial (Mavura, Chemelil, Saenyi, & Mavura, 2008). En semillas de moringa se encuentran agentes coagulantes caracterizados por ser proteínas diméricas catiónicas (peso molecular de 13 kDa y punto isoeléctrico entre 10-11), las cuales tienen también actividad antimicrobiana (Anwar & Rashid, 2007).…”
Section: Mecanismos Físico-químicos De Coagulación Naturalunclassified
See 1 more Smart Citation
“…Gomas (galactomananos) de semilla de Cassia obtusifolia también se han utilizado para la remediación de aguas residuales de aceite de palma (Shak & Wu, 2014), así como las gomas de semillas de Cassia angustifolia para la remoción de colorantes (Sanghi, Bhatttacharya, & Singh, 2002). Además, a polisacáridos como la amilopectina extraída del jugo de tubérculos de Maerua subcordata se atribuye el efecto coagulante para la clarificación de agua superficial (Mavura, Chemelil, Saenyi, & Mavura, 2008). En semillas de moringa se encuentran agentes coagulantes caracterizados por ser proteínas diméricas catiónicas (peso molecular de 13 kDa y punto isoeléctrico entre 10-11), las cuales tienen también actividad antimicrobiana (Anwar & Rashid, 2007).…”
Section: Mecanismos Físico-químicos De Coagulación Naturalunclassified
“…En semillas de moringa se encuentran agentes coagulantes caracterizados por ser proteínas diméricas catiónicas (peso molecular de 13 kDa y punto isoeléctrico entre 10-11), las cuales tienen también actividad antimicrobiana (Anwar & Rashid, 2007). Extractos líquidos de Maerua subcordata tuvieron efecto de remoción de turbidez debido a la influencia de amilopectinas contenidas en el jugo extraído del tubérculo de la planta (Mavura et al, 2008).…”
Section: Mecanismos Físico-químicos De Coagulación Naturalunclassified
“…Consequently, removing the big tuber will not harm the plant survival. One study in Kenya has 401 indicated that local people use M. subcordata for purification of turbid water (Mavura et al 2008). The tuber of the plant is also reported to be used for sorption of Cu (II) and Pb (II) (Kowanga et al 2012).…”
Section: Plants Usedmentioning
confidence: 99%
“…Even though the carbohydrate content is about 7.3 times greater (Compaoré et al 2011), this fraction which is also responsible for the particle coagulation does not seem to have much influence on the corresponding activity. The limited presence of the branched polysaccharides such as amylopectin which leads to effective coagulation in the roots extract of Maerua subcordata (Mavura et al 2008) could also be accounted for the decreased coagulation activity. Along with its reduced protein content, it is not surprising that M. oleifera is more efficient as the active agents have been identified to be that of protein nature (Ndabigengesere et al 1995).…”
Section: Phaseolus Angularismentioning
confidence: 99%
“…This explains its improved coagulation efficiency whereby the larger fraction of carbohydrate has dominating effect towards particle aggregations. The coagulation activity in the plant extracts such as those from the roots of M. subcordata (Mavura et al 2008) and seeds of Zea mays (Raghuwanshi et al 2002) has also been attributed to the presence of starch.…”
Section: Pisum Sativummentioning
confidence: 99%